RHO A versus RHO C. (c2014) - Dimassi, Saleh B. Al (2016)
Malignant astrocytomas are associated with high mortality rates; these tumors are highly invasive into adjacent areas of the normal brain. It has been established that Rho family of GTPases play a central role in regulation of cell migration and invasion. The Rho family is ras-related, consisting of the Rho, Rac, and CDC42 subfamilies. The Rho Protein has subtypes designated as RhoA, RhoB, RhoC, RhoD, RhoE, and RhoH genes. In this study we aim to look at the role both Rho A and Rho C play in protrusion formation where we found that upon RhoA knockdown protrusions are no longer formed, using 2D time lapse microscopy that shows the depletion of RhoA and RhoC leads to the decrease in 2D motility, RhoA knockdown decreases adhesion of cells in contrast RhoC knockdown increases adhesion of astrocytoma, and FRET based biosensors. In addition to study the role both proteins play in invadopodia formation which is not RhoA dependent according to our data, and cellular invasion where our results shows an increase in cell invasion upon both RhoA and RhoC knockdown. This study examines for the first time, the differential roles of RhoA and RhoC isoforms in astrocytoma motility and invasion.